2003
DOI: 10.1086/374181
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Dynamics under Time Limits

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…Using this monthly caseload (stock) data from the DHHS, Danielson and Klerman (2004) find evidence of an anticipatory drop in welfare participation in short time-limit states. Such a drop is consistent with the forward-looking behavior of welfare participants first highlighted by Grogger (2002) and Grogger and Michalopoulos (2003). The authors conclude that a relatively small share of the decline in caseloads during a period including the 1990's boom can be accounted for by changes in welfare policy.…”
Section: Testing Whether Time Limits Are a Binding Constraintsupporting
confidence: 75%
“…Using this monthly caseload (stock) data from the DHHS, Danielson and Klerman (2004) find evidence of an anticipatory drop in welfare participation in short time-limit states. Such a drop is consistent with the forward-looking behavior of welfare participants first highlighted by Grogger (2002) and Grogger and Michalopoulos (2003). The authors conclude that a relatively small share of the decline in caseloads during a period including the 1990's boom can be accounted for by changes in welfare policy.…”
Section: Testing Whether Time Limits Are a Binding Constraintsupporting
confidence: 75%
“…To assign all single mothers a subsidy would introduce measurement error to child care prices that far exceeds the error from leaving prices unadjusted. 15 Building on research by Grogger (2003) and Grogger and Michalopoulos (2003), I capture the effects of time limits through the dummy variable and its interaction with the age of the mother. Allowing the effect of time limits to vary by age accounts for the possibility that mothers save their welfare benefits until an employment shock occurs.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…All three found that families with younger children were more affected by time limits than households with older children. Grogger's (2003) findings suggest that time limits cause a 13% drop in welfare use -much lower than the 16-19% reported in Grogger (2004) and Grogger and Michalopoulos (2003) or the 28% reported by Kaushal and Kaestner. Moreover, variables such as the EITC also influence welfare participation.…”
Section: Introductionmentioning
confidence: 68%
“…Grogger and Michalopoulos (2003), Kaushal and Kaestner (2001), Keng et al (2002) and Grogger (2003Grogger ( , 2004a estimated the impact of a time limit dummy variable on labour supply decisions. Kaushal and Kaestner (2001) used a difference-in-difference method to estimate the impact of time limits on welfare caseloads and found that time limits increased employment and induced higher work effort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation